Comparison between traditional coal washability determination methods and the RhoVol density analyser, Q.P. Campbell, M. le Roux, and M. Fofana - Q. P. Campbell; M. Le Roux; M. Fofana (The Southern African Institute of Mining and Metallurgy, 2020)
The determination of densimetric information to predict coal washabilities is an important step in characterising the feed material, as well as the performance of operating plants. However, traditional methods like float-and-sink analysis are hazardous and time-consuming. This is especially true for finer particle size ranges, where very long settling times are required in a medium. De Beers Technologies recently developed a density analyser, known as the RhoVol, for use on diamondiferous kimberlite. Operating over size ranges from 25 mm down to 3 mm, it can determine the mass, volume, density, size and shape of all the particles in a given population and is thus able to provide information about the densimetric distribution on a single particle basis. A study was carried out to compare uncalibrated and calibrated RhoVol results to densimetric and size data obtained using traditional zinc chloride float-sink procedures, for three different coal samples in the size range 3 mm to 8 mm. The results indicate that the RhoVol can be used to provide simple, rapid and safe size-by-washability information for coal, provided proper pre-calibration is done, mainly to account for the effects of particle porosity in the density determination. Keywords: Coal washability determination, RhoVol, densimetric curve